The MPX5700AP Pressure Sensor Optimization for Blood Pressure Reading in The Design of Poltekad Electronic Detector Covid-19 (POLECTOR C-19) Using Oscillometer Method - Hanafi, Mohamad Imron; Ansori, Mohammad; Saefullah, Lalu (Pustaka Poltekad, 2021)
Abstract - At the beginning of 2020 the world was shocked by the presence of a virus that attacks the respiratory tract, a virus known as Coronavirus Disease-2019 (Covid-19). Based on this problem, how does the system detect Covid-19 suspects based on blood pressure. In this study, researchers used a survey method which directly took data in the hospital. Therefore, the optimization of the MPX5700AP pressure sensor has been successfully made. At this time the researchers conducted a study that used the oscillometer method to measure blood pressure supported by Arduino Uno, which in waves will produce systolic and diastolic blood pressure. Blood pressure monitoring is made capable of measuring blood pressure in the range of 40-240 mmHg and this system has a systolic pressure error of 4.024 mmHg, while the diastolic pressure error is -0.408 mmHg.